Working therapeutically with women in secure mental health settings - Jeffcote, Nikki, 1959-; Watson, Tessa, 1967- (Jessica Kingsley Publishers, 2004)
A pressing need for the integration of current practice, research and service development is addressed in this comprehensive book, which explores the experience of work with women in secure mental health settings. The first section offers different perspectives on the needs and situations of this minority population. It includes consideration of the differing needs of women and men, and key environmental and therapeutic issues highlighted by recent research and service provision. Further chapters cover clinical illustrations of work with women in different settings, including descriptions of i.
Keywords: Women prisoners -- Mental health services.; Women prisoners -- Mental health.; Mentally ill offenders -- Mental health services.; Female offenders -- Mental health services.; Forensic psychiatric nursing.; Mental health services.; Forensic psychiatry.; Psychiatric hospitals.; Mental Health Services; Prisoners -- psychology; Forensic Psychiatry; Hospitals, Psychiatric; Institutionalization; Mentally Ill Persons -- psychology; Women -- psychology; United Kingdom; Psychiatric Department, Hospital; Prisonnières -- Services de santé mentale.; Prisonnières -- Santé mentale.; Criminels vivant avec un trouble de santé mentale -- Services de santé mentale.; Criminelles -- Services de santé mentale.; Soins infirmiers médico-légaux en psychiatrie.; Services de santé mentale.; Psychiatrie médico-légale.; Hôpitaux psychiatriques.; Hôpitaux -- Services de psychiatrie.; psychiatric hospitals.; Psychotherapy.; Pathology.; SOCIAL SCIENCE -- Penology.; Psychiatric hospitals; Mental health services; Forensic psychiatry; Forensic psychiatric nursing; Mentally ill offenders -- Mental health services; Women prisoners -- Mental health; Women prisoners -- Mental health services